The role of immunity in mosquito-induced attenuation of malaria virulence. - Mackinnon, M (2014)
A recent study found that mosquito-transmitted (MT) lines of rodent malaria parasites elicit a more effective immune response than non-transmitted lines maintained by serial blood passage (non-MT), thereby causing lower parasite densities in the blood and less pathology to the host. The authors attribute these changes to higher diversity in expression of antigen-encoding genes in MT cf. non-MT lines. Alternative explanations that are equally parsimonious with these new data, and results from previous studies, suggest that this conclusion may be premature.